Establishing locally derived reference intervals for full blood count parameters and white cell differential counts in the Western Cape region of South Africa - DeKoker, Annemarie (Department of Pathology, 2022)
Background: The recognised variation observed in normal haematological parameters in different populations and geographic locations, emphasizes the need to establish locally derived reference intervals (RIs) with appropriate representation of the various ethnic groups. Accurate RIs are essential to distinguish between health and disease. Objective: To establish locally derived RIs for full blood count (FBC) and white blood cell (WBC) differential count parameters in healthy adults in the Western Cape region of South Africa. Methods: A prospective, descriptive study was performed, utilizing blood samples of healthy first-time blood donors, presenting voluntarily for blood donation to the Western Cape Blood Service (WCBS) between November 2016 and October 2017. African, Coloured and Caucasian participants aged between 18 and 60 years of age were included based on convenience sampling. Participants testing positive for human immunodeficiency virus (HIV), hepatitis B and C viruses (HBV, HCV) and syphilis, and those with serum ferritin levels outside the reference range were excluded. Donors with an elevated serum ferritin were also excluded. Reference intervals were derived using non-parametric statistical methods and expressed to include the central 95% of the sample population (2.5th to 97.5th percentiles). Outliers for individual parameters were identified and excluded from the analysis. Results: A total of 376 females and 244 males were included for analysis; 31.61% were African, 39.68% Coloured and 28.71% Caucasian. For all race groups combined, gender-based differences were found in most FBC parameters, including the haemoglobin (Hb), WBC count, neutrophil count and platelet count. When comparing RIs for males and females in the three ethnic groups, statistically significant differences were found for parameters including the Hb, WBC count and red cell indices. There were no significant differences in the absolute eosinophil counts and mean cell volume (MCV) in females, and platelet counts in males. The ranges differed for a number of FBC variables compared to the National Health Laboratory Service (NHLS) coastal reference ranges in current use. Conclusion: Locally established and population-specific RIs are essential for accurate interpretation of blood counts. Implementation of separate RIs for the main ethnic groups in the Western Cape should be considered and would have implications for the diagnosis of anaemia and other blood count abnormalities as well as decision rules on haemoglobin levels for blood donor deferral.